2002
DOI: 10.4141/a01-045
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol addition and conservation of fresh and cryopreserved ram spermatozoa

Abstract: . 2002. Glycerol addition and conservation of fresh and cryopreserved ram spermatozoa. Can. J. Anim. Sci. 82: 347-356. Fresh extended ram semen has a short fertile lifespan whereas acceptable fertility with cryopreserved semen is achieved only by laparoscopy, which limits widespread artificial insemination in sheep. Although glycerol is considered essential for freezing spermatozoa, it is often included in extenders for short-term storage at above-freezing temperatures. To test the hypothesis that glycerol red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…Regardless, these data provided evidence that partial or full cryopreservation induces precocious capacitation of bull sperm. Similar findings have also been reported for different species, including mice (Fuller and Whittingham 1996), sheep (Pérez et al 1996;Morrier et al 2002), and pigs (Gillan et al 1997). Capacitation, though a necessary step toward fertilisation, is known to destabilise the sperm membranes (Harrison 1996).…”
Section: Cryopreservation and Prematuresupporting
confidence: 66%
“…Regardless, these data provided evidence that partial or full cryopreservation induces precocious capacitation of bull sperm. Similar findings have also been reported for different species, including mice (Fuller and Whittingham 1996), sheep (Pérez et al 1996;Morrier et al 2002), and pigs (Gillan et al 1997). Capacitation, though a necessary step toward fertilisation, is known to destabilise the sperm membranes (Harrison 1996).…”
Section: Cryopreservation and Prematuresupporting
confidence: 66%
“…Pelufo et al (2015) demonstrated that the best procedure for ram semen cryopreservation in hypertonic disaccharide-containing diluents is the addition of glycerol after the cooling process, at 5 o C, than before it at 30 o C. Differences between 30 o C and 5 o C for spermatozoa quality were noticed just for HOST (hypo-osmotic swelling test), as plasma membrane showed higher sensitivity to glycerol addition at 30 o C. Moreover, Anel et al (2003) suggested that freezing of ram semen in a test-fructose-egg yolk medium containing 4% glycerol in a two-step dilution (to 2% at 35 o C and to 4% at 5 o C) along with a programmable biofreezer (-20 o C/min), results in good field fertility rate. Furthermore, according to Gil et al (2003) the addition of glycerol in a traditional milk extender supplemented with 5% egg yolk at 15 o C does not present any improvement in thawed semen quality compared to 5 o C. In contrast with the two steps dilution protocol studies, Morrier et al (2002) reported that the addition of glycerol either immediately after collection (one-step) or at 5° C (two-steps) does not affect motility and viability of frozen-thawed ram sperm.…”
Section: ) Research Concerning "Glycerol" Concentration and Additionmentioning
confidence: 96%
“…At 8 and 24 h post-collection, one sealed straw of semen was cut open (with clean scissors) and diluted (about 32-fold; to 50 × 10 6 sperm mL -1 ) in synthetic oviductal fluid (SOF-m; Morrier et al 2002). The SOF-m was composed of 108 mM NaCl, 7.2 mM KCl, 1.2 mM KH 2 PO 4 , 25 mM NaHCO 3 , 5 mM CaCl 2 , 0.5 mM MgCl 2 , 1.5 mM glucose, 3.3 mM sodium lactate, 0.33 mM sodium pyruvate, 1 mM glutamine, 20 µM penicillamine, 10 µM hypotaurine, and 50 mg L -1 gentamycin.…”
Section: Semen Preparation and Conservationmentioning
confidence: 99%
“…For the assessment of sperm motility, three 2-µL samples of sperm in SOF-m (~50 × 10 6 cells mL -1 ) were deposited into a 10-µm Makler counting chamber (Sefi-Medical Instruments, Haifa, Israel) placed on the motility analyser (Hamilton Thorn Research, Beverly, MA) as described by Morrier et al (2002). At least 200 cells from five random fields were recorded.…”
Section: Sperm Motility Analysismentioning
confidence: 99%
See 1 more Smart Citation